2019
DOI: 10.1590/1519-6984.179134
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mother nutrition during pregnancy and/or lactation on offspring food preference in experimental models

Abstract: Understanding associations between food preferences and maternal nutrition during pregnancy and lactation could inform efforts to understanding the obesity mechanisms and provide insight to prevent it. Objective: To identify studies that investigated the effects of nutritional interventions during the pregnancy and lactation on the food preferences of offspring. Method: The review was conducted with search for articles in the databases: Scopus, Pubmed, Medline, LILACS, Scielo and Science Direct. Exclusion crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…For example, Haramaya mothers in this sample who prefer foods that include animal sources were five times more likely to feed their children adequate diversity than those who avoid it. This aligns with a study conducted in experimental models that the mother’s food preference and nutrition during pregnancy and lactation affect the offspring’s food preference and neural components 68. Foods disliked by mothers tended not to be offered to children 69.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…For example, Haramaya mothers in this sample who prefer foods that include animal sources were five times more likely to feed their children adequate diversity than those who avoid it. This aligns with a study conducted in experimental models that the mother’s food preference and nutrition during pregnancy and lactation affect the offspring’s food preference and neural components 68. Foods disliked by mothers tended not to be offered to children 69.…”
Section: Discussionsupporting
confidence: 86%
“…This aligns with a study conducted in experimental models that the mother’s food preference and nutrition during pregnancy and lactation affect the offspring’s food preference and neural components. 68 Foods disliked by mothers tended not to be offered to children. 69 A child’s preferences depend on early exposure to family foods that contribute to shaping food preferences later.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the feeding practices in the first years of life, maternal influences might also determine the dietary patterns at later ages. Accumulating evidence from experimental studies indicates that maternal intake of foods rich in fat, sugar, and sodium during pregnancy and lactation is accompanied by a higher preference for these foods in their offspring (60,61) . Similarly, several observational studies have shown a positive association between maternal and child dietary intakes and diet quality (62)(63)(64) .…”
Section: Accepted Manuscriptmentioning
confidence: 99%